Simultaneous determination of trace level riot control agents in environmental water by solid‐phase microextraction and gas chromatography coupled with a flame ionization detector. Issue 14 (11th May 2022) - Hao, Shangpeng; Wang, Haitao; Zhao, Wenbo; Sun, Chao; Gao, Runli; Zhang, Yuanpeng
Abstract : In this paper, a direct immersion solid‐phase microextraction procedure for the simultaneous analyses of four primary riot control agents: 2‐chloroacetophenone, o‐chlorobenzylidene malonitrile, dibenz(b, f)‐1, 4‐oxazepine, and oleoresin capsicum at μg/L concentration from environmental water was developed. Several parameters that influence the extraction effectiveness were investigated, including fiber type, extraction temperature, extraction time, starring rate, and salinity. Under the recommended conditions, the optimized method had reasonable linearity and accuracy. The average recovery of this method ranged from 84 to 108.1%. The limit of detection for all the analytes ranged from 0.2 to 3 μg/L and the limit of quantification ranged from 1 to 10 μg/L, respectively. A relative standard deviation from 3.0 to 4.3% can be achieved depending on the compounds. The procedure was applied to analyze all the four riot control agents simultaneously in several environmental samples.